2018
DOI: 10.1002/adfm.201706815
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance n‐ and p‐Type Field‐Effect Transistors Based on Hybridly Surface‐Passivated Colloidal PbS Nanosheets

Abstract: Colloidally synthesized nanomaterials are among the promising candidates for future electronic devices due to their simplicity and the inexpensiveness of their production. Specifically, colloidal nanosheets are of great interest since they are conveniently producible through the colloidal approach while having the advantages of two-dimensionality. In order to employ these materials, according transistor behavior should be adjustable and of high performance. It is shown that the transistor performance of colloi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 57 publications
(196 reference statements)
1
8
0
Order By: Relevance
“…[ 49,50 ] These measurements (shown in Figures S10c and S11 in the Supporting Information) reveal that the Cl content on the surface of the zigzag wires (15%) is lower compared to the straight nanostripes (20%) and especially compared to the previously studied PbS nanosheets (30–60%). [ 51 ] In addition, the HAADF–XEDS measurements show a lower Cl content in the whole crystal of the zigzag wires compared to the straight stripes (Figure S12, Supporting Information). Therefore, it can be concluded that the performed synthesis fulfils this requirement and preserves metallic behavior of the wires by reducing the Cl content on the surface of the crystal.…”
Section: Discussionmentioning
confidence: 99%
“…[ 49,50 ] These measurements (shown in Figures S10c and S11 in the Supporting Information) reveal that the Cl content on the surface of the zigzag wires (15%) is lower compared to the straight nanostripes (20%) and especially compared to the previously studied PbS nanosheets (30–60%). [ 51 ] In addition, the HAADF–XEDS measurements show a lower Cl content in the whole crystal of the zigzag wires compared to the straight stripes (Figure S12, Supporting Information). Therefore, it can be concluded that the performed synthesis fulfils this requirement and preserves metallic behavior of the wires by reducing the Cl content on the surface of the crystal.…”
Section: Discussionmentioning
confidence: 99%
“…[ 208 ] These rock‐salt PbS nanosheets showed high performance in FET applications, which can be either n‐ or p‐type depending on the surface defects introduced. [ 209 ] Recently, this group also reported the spintronics of rock‐salt PbS with an unusual selection mechanism of carrier excitation, which can be tuned by the gate voltage and thickness of the materials. [ 210 ] Apparent quantum confinement was observed when the thickness of PbS was reduced from 6 to 2 nm.…”
Section: Group Iv–vimentioning
confidence: 99%
“…Exfoliated 2D phosphorene nanosheets without encapsulation are found to chemically degrade upon exposure to ambient conditions urgently [137]. Passivation is a prominent approach to decrease surface degradation, which not only decreases the surface roughness but also avoids the formation of chemisorbed species [157162]. Wood et al investigated how exfoliated black phosphorus degrades to oxygenated phosphorus compounds in the ambient condition through a systematical suite of microscopy and spectroscopy techniques [36].…”
Section: Integration and Characterization Of 2d Pnictogen Fetsmentioning
confidence: 99%